Tax Education According to the Latest Regulations for Vocational High School Taxation Teachers in West Sumatra: Edukasi Pajak Sesuai Aturan Terbaru bagi Guru Perpajakan Sekolah Menengah Kejuruan di Sumatera Barat - Fefri Indra Arza; Sari, Vita Fitria; Cheisviyanny, Charoline; Pebriyani, Dewi; Ridhaningsih, Fitria (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
In last 10 years tax compliance ratio in Indonesia continues to increase as well as the realization of tax revenues which have been able to exceed the target in the last 2 years. However, the tax ratio is still relatively low and homework for the government. One of the factors that influences the tax ratio is the level of tax compliance, which can be improved through a tax education program. In this activity, the target for tax education are members of the MGMP Accounting and Banking in West Sumatra Province who teach taxation subjects. The material that will be provided is the latest taxation regulations, namely income tax article 21 which will be effective from January 1, 2024 and the Core Tax Administration System (CTAS) which will be effective in July 2024. This community service has succeeded in increasing participants' understanding in calculating income tax article 21 according to the latest regulations, and is expected to be used as a reference in revising teaching materials for taxation subjects.